Control of an underactuated double-pendulum overhead crane using improved model reference command shaping: Design, simulation and experiment - Jaafar, H.I.; Mohamed, Z.; Mohd Ashraf, Ahmad; Wahab, N.A.; Ramli, L.; Shaheed, M.H. (Academic Press, 2021)
This paper presents a new control scheme based on model reference command shaping (MRCS) for an overhead crane, with double-pendulum mechanism effects. The approach has an advantage in achieving an accurate trolley positioning, with low hook and payload oscillations, under various desired trolley positions and parameter uncertainties, without the requirement for measurement or estimation of system parameters. These are challenging in practice. The previously developed MRCS algorithm is improved in order to reduce its design complexity, as well as to ensure that it can be augmented with a feedback controller so that a concurrent controller tuning can be realised. The combined MRCS and feedback controller is used to achieve both, precise trolley positioning, and low hook and payload oscillations. To evaluate the effectiveness and the robustness of the approach, simulations and experiments using a nonlinear model and a laboratory double-pendulum crane are carried out. Under various desired positions and parameter uncertainties that involve varying the cable lengths (payload hoisting) and the payload mass variations, the superiority of the proposed approach is confirmed by achieving higher hook and payload oscillation reductions when compared with a recently proposed feedback controller. In addition, the desired trolley positions are achieved with smoother responses.